Transcriptional analysis of cell cycle regulators during the induction phase of diapause in Chymomyza costata. - Šimůnková, Petra (Jihočeská univerzita, 2011)
The changes of relative mRNA levels of seven different genes, coding for key cell cycle regulatory factors (Cyclins D and E, kinases Wee1 and Myt1, Phosphatase Cdc25 (String), Dacapo (p27), and Pcna) were performed using qRT-PCR method. Two reference genes (Rp49 and ?-tubulin) served as a background. Significant transcriptional response to photoperiodic transfer were observed for two genes. While the relative levels of Dacapo mRNA increased during the rapid entry into G2 arrest, the Pcna expression was significantly downregulated during the beginning of G0/G1 arrest. Moderate transcriptional upregulations of the genes coding for two cell cycle inhibitory kinases, Wee1 and Myt1 accompanied the entry into diapause. The other genes were expressed equally in all photoperiodic conditions.
Transcriptional analysis of cell cycle regulators during the induction phase of diapause in Chymomyza costata.